A PHENOMENOLOGICAL STUDY OF LIVED EXPERIENCES OF PARENTS AT A YOUNG AGE - Louie Petere Gula (Universitas Indraprasta PGRI, 2022)
This study aims to find out the experiences encountered by the parents at a very young age considering their maturity and financial capabilities. This study highlights the form of gathering data which is conducted using an interview. This is done in a dyad form wherein only one respondent is involved in the interview. The term qualitative research refers to the collection and analysis of non-numerical data and is sometimes based on a phenomenon which could be in a form of a survey questionnaire or an interview. Based on the data and analysis; poverty is the main reason for entering a marriage. Generally, the kind of life wished by everybody to have was not merely dictated by fate, it was a manifestation of personal choice. Each individual has their own choices in what to pursue and to sacrifice, the only sure thing that a person can do is to prepare for the consequences that await in the process